Bloodstream infection caused by KPC-producing Klebsiella pneumoniae resistant to ceftazidime/avibactam: epidemiology and genomic characterization. (April 2020) - Gaibani, P.; Re, M.C.; Campoli, C.; Viale, P.L.; Ambretti, S.
Abstract: Objectives: The aim of this study was to evaluate the incidence of ceftazidime/avibactam resistance among Klebsiella pneumoniae carbapenemase (KPC)-producing K. pneumoniae (KPC-Kp) strains isolated from patients with bloodstream infection. Methods: We collected 120 carbapenemase producing Enterobacteriaceae (CPE) strains from unique patients hospitalized in two Italian hospitals between January 2018 to February 2019. Strains were phenotypically characterized for the type of carbapenemase production and susceptibility to ceftazidime/avibactam. Ceftazidime/avibactam-resistant strains were characterized by whole-genome sequencing. Results: During the study period, we characterized 105 (87.5%) KPC producers among a total of 120 CPE strains. Ceftazidime/avibactam resistance was found in three KPC-Kp strains isolated from patients with no history of previous ceftazidime/avibactam-based treatment. Of note, two out of three ceftazidime–avibactam-resistant KPC-Kp were also resistant to meropenem/vaborbactam. Genomic characterization showed that a ceftazidime/avibactam-resistant KPC-Kp harboured a mixed population with D179Y mutated KPC-2, while the other two ceftazidime–avibactam-resistant KPC-Kp possessed non-functional ompK35-ompK37 and mutated ompK36 porins associated with higher copy number of bla KPC gene. Conclusions: Our results showed that incidence of ceftazidime/avibactam resistance emerged in KCP-Kp strains independently from previous antimicrobial exposure. Resistance to ceftazidime/avibactam was associated with mutations within the bla KPC gene or porin deficiency associated with higher bla KPC copy number and is also related to the meropenem/vaborbactam resistance.